Autonomia da Polícia Judiciária Federal: evolução legislativa com foco na última década no Brasil - Nelson, Luiz Carlos Nóbrega (2023)
This work aims to demonstrate the evolution of the Brazilian Police, in this case more represented by the Federal Police, mainly in the time span of the last decade. Part of the legislative evolution that improved the Brazilian legal framework, with the construction and the move towards more autonomous judicial police and according to the dictates of a Democratic State of Law. It is important to emphasize that there is no pretension to state which is the ideal model for judicial police responsible for investigating criminal conduct, but only to consolidate in a documentary way the progress made in this construction over time.